Deprivation and access to work in Dublin City: The impact of transport disadvantage. (September 2016) - Ahern, Aoife; Vega, Amaya; Caulfield, Brian
Abstract: Ireland's economy underwent a period of rapid expansion between 1995 and 2007, accompanied by a boom in construction. The subsequent decade saw a rapid decline in construction as Ireland went through an unprecedented recession. This paper examines how this boom and bust has influenced deprivation and accessibility in Dublin. The paper examines, through a logit model, links between transport disadvantage, deprivation and employment accessibility in the city. The paper concludes that links exist between deprivation and accessibility in the city, in particular in the newer peripheral suburbs, leaving these areas open to risk of transport poverty.